If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2t + 6) = 0 Reorder the terms: 3(6 + 2t) = 0 (6 * 3 + 2t * 3) = 0 (18 + 6t) = 0 Solving 18 + 6t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6t = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6t = 0 + -18 6t = 0 + -18 Combine like terms: 0 + -18 = -18 6t = -18 Divide each side by '6'. t = -3 Simplifying t = -3
| 12y+y^2=6y | | 535(64+646)53= | | 7=-2(-3-y) | | 5+2y=15 | | -3(n+2)=12 | | 2(4-3m)=13 | | 3(5+2x)=8(5+x) | | 64-4x=32x+24 | | 5(x-6)=-15 | | (6t-1)+(4t+2)+(7t+3)+3t=124 | | 4y^3-2=1y-8y^2 | | 6x+10=-120-7x | | 5(2+3+x)=110 | | 2y+10=2y+5 | | 2j(7j^2+jk^2+5k)-9k(-2j^2k^2+2k^2+3j)=0 | | t-4=21 | | t-4=24 | | 2.5x+1.5x=6 | | 15x^3-12x^2+3x= | | -20=-4+z | | -20=-4+7 | | 3x-50=1 | | 6+1x-10x^2=0 | | 7x-50=1 | | -10=-n+2-2n | | -14x^3-7x^2= | | 3x*27723355675= | | (x-6)7=49 | | 3x*2= | | 12=2x-7x-8 | | 9x^2+6x-1=0 | | 62-4x=14x+18 |